Long-Term Endurance and Power Training May Facilitate Motor Unit Size Expansion to Compensate for Declining Motor Unit Numbers in Older Age - Piasecki, M.; Ireland, A.; Piasecki, J.; Degens, H.; Stashuk, D. W.; Swiecicka, A.; Rutter, M. K.; Jones, D. A.; McPhee, J. S. (Frontiers in Physiology, 2019)
The evidence concerning the effects of exercise in older age on motor unit (MU) numbers, muscle fibre denervation and reinnervation cycles is inconclusive and it remains unknown whether any effects are dependent on the type of exercise undertaken or are localised to highly used muscles. Motor unit characteristics of the vastus lateralis (VL) were assessed using surface and intramuscular electromyography in eighty-five participants, divided into sub groups based on age (young, old) and athletic discipline (control, endurance, power). In a separate study of the biceps brachii (BB), the same characteristics were compared in the favoured and non-favoured arms in eleven masters tennis players. Muscle size was assessed using MRI and ultrasound. In the VL, the CSA was greater in young compared to old, and power athletes had the largest CSA within their age groups. MU potential (MUP) size was larger in all old compared to young (p < 0.001), with interaction contrasts showing this age-related difference was greater for endurance and power athletes than controls, and MUP size was greater in old athletes compared to old controls. In the BB, CSA did not differ between favoured and non-favoured arms (p = 0.575), but MUP size was larger in the favoured arm (p < 0.001). Long-term athletic training does not prevent age-related loss of muscle size in the VL or BB, regardless of athletic discipline, but may facilitate more successful axonal sprouting and reinnervation of denervated fibres. These effects may be localised to muscles most involved in the exercise.